(untitled) (The Pretoria Student Law Review, 2021)
To attempt any debate or discussion on the law of adultery in a Roman Dutch common law jurisdiction, without tracing the development of the law in this regard under Roman law would be a gross injustice. This is because the common law in Zimbabwe is largely Roman Dutch law with graftings of English principles.1 This is the law that was applied at the Cape of Good Hope as at 10 June 1891, as evidenced by section 89 of the old Zimbabwe Constitution.2 It would be of no benefit to explore English Law in this discussion for the simple reason that in England, all references to adultery have been deleted from the law.3 It is no longer a crime, no longer gives rise to a third party claim for delictual damages and is no longer included in the divorce statutes.4 Since Roman Dutch law is the foundation of our common law, it is important to understand the lex Julia which was the cornerstone of matrimonial law under Roman law.5 The lex Julia was an ancient Roman Law which was a moral code of conduct. It was a creation of patriarchy. Roman law was sometimes extreme when it came to adultery and it gave the husband powers of self-help.6 One cannot over-emphasise how serious adultery was perceived in the Roman law society. Adultery was a crime so serious that it attracted a severe punishment, sometimes even capital punishment, and this could be executed either by the couples’ guardian or the husband.7 Although murder is an unfathomable punishment for any marital misdemeanour, adultery included, it was justifiable under the circumstances.8 The law cannot however afford to stay stagnant hence, these ancient harsh penalties no longer find a place in our current Zimbabwean society as shall be highlighted below.